MORAL VALUES AS AN IMPORTANT FACTOR FORMATION OF A HEALTHY LIFESTYLE (British Journal of Global Ecology and Sustainable Development, 2023)
The article analyzes the issues of healthy lifestyle, the role of moral values in its formation and development. The role and importance of oriental manners, universal ideals, and moral values in the development of a spiritually mature person is considered. The moral and moral integrity of a person and its standards are shown.The role and importance of moral values in the formation of a healthy lifestyle among the citizens of Uzbekistan and young people is shown.